Bulgarians, Cumans, Teutons, and Vlachs in the First Decades of the Thirteenth Century - Ivanov, Ivelin (Studia Ceranea, 2022)
The article refers to some aspects of the history of today’s Bulgarian and Romanian territories, going back to the end of the 12th and the beginning of the 13th century. First, the author emphasizes the impact of the Teutonic Order in Burzenland on Bulgarian-Cuman relations in the period under question. The article provides a different alternative viewpoint on the events of the second decade of the 13th century. Contrary to researchers who focus on the South and the Bulgarian-Latin conflict, the author seeks a solution to the problem by analyzing events in the North, reaching the lands of Burzenland region in Eastern Transylvania. He analyses the Teutonic-Cuman conflict of 1211–1222 and the success of the Teutons in Cumania after 1215. The author concludes that the dramatic change in the Bulgarian-Cuman relations could be explained by a new source of military and political influence that emerged in the second decade of the 13th century – the Teutonic Order. Next, the paper is aimed at the highly discussed and controversial issue of Bulgarian-Vlach relations during the rule of the Assenid dynasty. Based on the written sources, the author explains the mass presence of Vlachs in the actions of the first Assenids with specific social, economic and political factors in the last two decades of the 12th and the beginning of the 13th century.